Diagnostic applications of the "pattern" electroretinography and visual evoked potentials in the evaluation of disorders of visual pathway function in Parkinson’s disease - Stamenović Jelena; Živadinović Biljana; Đurić Vanja; Ljubisavljević Srđan (Vojnosanitetski Pregled)
Background/Aim. In spite of continuous research efforts, specific laboratory, neuropsychological or neurophysiological tests for diagnosing Parkinson’s disease (PD) have not been established. The aim of the study was to determine the nature and extent of visual pathway disorders on “pattern” electroretinography (PERG) and visual evoked potentials (VEPs) in certain stages of PD. Methods. The study was carried out in a group of 60 persons of both sexes who were suffering from idiopathic PD at the I–IV stage of the disease according to the Hoehn and Yahr scale, and 30 healthy persons in the control group. The battery of noninvasive neurophysiological tests was used to estimate the functional status of the visual pathway − PERG and VEPs. Results. In the early phase of PD, there was a linear increase in the latency of the wave N50 of the PERG and the wave P100 of the VEPs, with a significant extension of the latency of the N50 and P100 waves in subsequent stages of PD. Diagnostic application of the PERG and VEPs enabled the confirmation of a disorder in the visual pathway function in PD. Conclusion. Applied neurophysiological techniques may record early changes in the function of retinal structures and the optic nerve in PD, which might be significant from both the diagnostic and therapeutic aspects.